Analisis Kepemimpinan, Pelatihan, dan Disiplin Kerja terhadap Kinerja Pegawai pada Dinas Perhubungan Kabupaten Nabire - Clint William Johanes Ferdinandus; Baharuddin; Natalia Paranoan (Paulus Journal of Accounting (PJA), 2024)
This research aims to determine and analyze the influence of leadership, training, and work discipline on employee performance at the Nabire Regency Transportation Service. The sample that will be used is 40 employees. The data analysis method that will be used in this research is multiple linear regression analysis after fulfilling the classical assumption test. The data used is primary data collected using a questionnaire distributed directly to employees of the Nabire Regency Transportation Service Office. The results of this research show that the leadership and work discipline variables have a significant effect on employee performance, while the training variable does not have a significant effect on employee performance at the Nabire Regency Transportation Service.